Seasonal growth dynamics of the seagrass Zostera caulescens on the eastern coast of Korea - Kim, Jong-Hyeob; Park, Sang Hoon; Kim, Young Kyun; Kim, Seung Hyeon; Park, Jung-Im; Lee, Kun-Seop (Ocean science journal, 2014)
Zostera caulescens is an endemic seagrass species in Northeastern Asia. Estimated distributional area of this species is approximately 1–5 km 2 on the coasts of Korea. Because Z. caulescens has a very limited distribution, the growth dynamics of Z. caulescens is little known in the coastal waters of Korea. In the present study, we investigated the growth dynamics of Z. caulescens in relation to coincident measurements of environmental factors, such as underwater irradiance, water temperature, and nutrient availability. The study was conducted on a monotypic meadow of Z. caulescens in Uljin on the eastern coast of Korea from September 2011 to September 2012. Shoot density and biomass of Z. caulescens showed distinct seasonal variations, and exhibited strong correlations with water temperature suggesting that the seasonal growth of this species was regulated by water temperature. Shoot density and biomass rapidly decreased during the high water temperature period in summer, and thus Z. caulescens is considered a cold water adapted species like other temperate seagrass species on coasts of Korea. Biomass of photosynthetic leaf tissues on reproductive shoots was approximately 4 times higher than that on vegetative shoots. The height of reproductive shoots ranged from 1.2 m in February 2012 to 3.2 m in August 2012, whereas the height of vegetative shoots was usually less than 1.0 m. Leaf tissues on reproductive shoots probably received much more light for photosynthesis than those on vegetative shoots. Thus, reproductive shoots may play an important role in total production of Z. caulescens .